Adopting Business Intelligence to Enhance Cross-Dock Operations - Jakub Andar; Jakub Dyntar (Acta Informatica Pragensia)
Background: Cross-docking optimization plays a crucial role in supply chain management by enhancing efficiency, reducing costs and streamlining operations. However, challenges arise from inaccurate data and a lack of digital tools to support decision making. Objective: The objective of this study was to integrate business intelligence (BI) tools with cross-dock operation data to optimize warehouse layout and improve decision making processes. Methods: A combination of Microsoft Visio and Microsoft Power BI was used to visualize and optimize warehouse layout based on historical cross-dock operation data. The methodology focused on integrating real-time data with spatial layout visualization to minimize total travel distance within the warehouse. Results: The integration of BI tools led to a 10% reduction in total travel distance, enhancing operational efficiency and reducing costs. The study demonstrates that BI-based decision support tools offer significant advantages over traditional optimization methods. However, challenges remain in scalability, real-time adaptability and user adoption. Conclusion: The proposed BI-driven solution improved warehouse layout optimization and facilitated data-driven decision making. Future research should explore the integration of BI with other optimization techniques and investigate its scalability in different warehouse environments.